2020
DOI: 10.1093/ajcp/aqaa089
|View full text |Cite
|
Sign up to set email alerts
|

Placental Pathology in COVID-19

Abstract: Objectives To describe histopathologic findings in the placentas of women with coronavirus disease 2019 (COVID-19) during pregnancy. Methods Pregnant women with COVID-19 delivering between March 18, 2020, and May 5, 2020, were identified. Placentas were examined and compared to historical controls and women with placental evaluation for a history of melanoma. Results … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

49
577
9
40

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 566 publications
(675 citation statements)
references
References 42 publications
49
577
9
40
Order By: Relevance
“…Increased intervillous brin deposition in relation to COVID-19 has also been observed by Shanes et al [4] and Baergen and Heller [5] in PCR-negative third trimester placentas. Moreover, this nding has been described in a small series of placentas delivered from pregnant women with severe acute respiratory syndrome caused by the SARS-COV virus during the 2003 epidemic [10].…”
Section: Discussion Main Ndings -Tendency Toward Thrombosis and Brin supporting
confidence: 69%
See 1 more Smart Citation
“…Increased intervillous brin deposition in relation to COVID-19 has also been observed by Shanes et al [4] and Baergen and Heller [5] in PCR-negative third trimester placentas. Moreover, this nding has been described in a small series of placentas delivered from pregnant women with severe acute respiratory syndrome caused by the SARS-COV virus during the 2003 epidemic [10].…”
Section: Discussion Main Ndings -Tendency Toward Thrombosis and Brin supporting
confidence: 69%
“…As of the time of this writing vertical SARS-COV-2 transmission remains controversial, while viral RNA has been detected in some placentas of COVID-19-affected mothers suggesting placental infection [1][2][3]. Emerging data on COVID-19-induced placental pathology are still limited [4,5]. We herein present in detail the placental pathology in two cases of pregnant women mildly affected with COVID-19 at term, and describe the pathological changes, including novel ndings not previously reported, along with their pathophysiological correlates.…”
Section: Introductionmentioning
confidence: 99%
“…Miscarriages and premature births to COVID-19-positive pregnant women have also been reported (7)(8)(9). Recently, a study showed that placentas from COVID-19-positive pregnant women displayed injury (10). Finally, SARS-CoV-2 was also detected in semen (11).…”
Section: Main Textmentioning
confidence: 95%
“…The placentas showed features of maternal vascular malperfusion, most prominently decidual arteriopathy and increased incidence of chorangiosis. Although, placental swabs were not performed which makes it unclear whether it was a local phenomenon or a systemic phenomenon [5]. Similarly, Hosier et al showed similar risk factors for maternal vascular malperfusion, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Lopes de Sousa et al published a systematic review in June 2020 and concluded that there is no concrete evidence for vertical transmission of COVID-19 but acknowledged that signi cant knowledge gaps exist and they cannot rule out this possibility [4]. The presence of COVID-19 has been assessed in neonates born to COVID-19 positive mothers by examining the placenta, and carrying out nucleic acid testing on breast milk and vaginal mucus [5][6][7].…”
Section: Introductionmentioning
confidence: 99%